The role of cellular senescence in neurodegenerative diseases - Wang, Yating; Kuca, Kamil; You, Li; Nepovimova, Eugenie; Heger, Zbynek; Valko, Marian; Adam, Vojtech; Wu, Qinghua; Jomova, Klaudia (Archives of toxicology, 2024)
Increasing evidence has revealed that cellular senescence drives NDs, including Alzheimer's disease (AD) and Parkinson's disease. Different senescent cell populations secrete senescence-associated secretory phenotypes (SASP), including matrix metalloproteinase-3, interleukin (IL)-1α, IL-6, and IL-8, which can harm adjacent microglia. Moreover, these cells possess high expression levels of senescence hallmarks (p16 and p21) and elevated senescence-associated β-galactosidase activity in in vitro and in vivo ND models. These senescence phenotypes contribute to the deposition of β-amyloid and tau-protein tangles. Selective clearance of senescent cells and SASP regulation by inhibiting p38/mitogen-activated protein kinase and nuclear factor kappa B signaling attenuate β-amyloid load and prevent tau-protein tangle deposition, thereby improving cognitive performance in AD mouse models. In addition, telomere shortening, a cellular senescence biomarker, is associated with increased ND risks. Telomere dysfunction causes cellular senescence, stimulating IL-6, tumor necrosis factor-α, and IL-1β secretions. The forced expression of telomerase activators prevents cellular senescence, yielding considerable neuroprotective effects. This review elucidates the mechanism of cellular senescence in ND pathogenesis, suggesting strategies to eliminate or restore senescent cells to a normal phenotype for treating such diseases.
Keywords: stárnutí buněk; Telomere Shortening; Neurodegenerative Diseases; signální transdukce; Alzheimerova nemoc; Alzheimer Disease; Cellular Senescence; amyloidní beta-protein; Signal Transduction; Senescence-Associated Secretory Phenotype; neurodegenerativní nemoci; zkracování telomer; Animals; lidé; Amyloid beta-Peptides; Humans; zvířata; sekreční fenotyp asociovaný se senescencí; Parkinson Disease; Parkinsonova nemoc